Holistic coaching style on personal attributes and proficiency of volleyball athletes - Aquino, John Michael D; Jolo, Mark Ulysses (UIR Press, 2024)
Background Problems: The significance of holistic coaching has been widely recognized. Meanwhile, there has not been much research done on how holistic coaching affects athletes’ personal attribute proficiency for the reason to investigate in order to better prepare their own skills for the demanding needs of volleyball. Research Objectives: The research aims to explore the holistic coaching on the athletes’ personal attributes and proficiency. Specifically, the researchers try to answer the status of implementing a holistic coaching style of volleyball athletes, in particular to clear communication, decision-making, goal-orientated, and result-driven. In addition, to determine the level of athletes personal attributes proficiency concerning skill development, teamwork, discipline, and sportsmanship. Methods: This study used a descriptive research approach, and the respondents consist of volleyball athletes, which were chosen purposefully. Additionally, the validated survey questionnaire was utilised as a primary data gathering tool. Findings and Results: The results reiterated that the status of implementing holistic coaching styles of volleyball athletes and personal attributes were highly observed and acceptable among the respondents. Likewise, the correlation of the different holistic coaching styles with each athlete’s personal attribute using Pearson’s correlation coefficient (r) has a significant correlation with the moderate to strong positive degree. Conclusion: These results highlight the significance of adjusting coaching strategies to the unique characteristics of each athlete while placing a strong emphasis on methods that are result-driven, goal-orientated, involve clear communication, and involve sound decision-making. Therefore, in order to maximise player growth and team performance, coaches should place a high priority on improving these coaching styles.